The Classroom Climate According to Grant Holders 18 (Becarios 18) and Regular Students from a Private University in Lima - Anaya, Julio B. (2015)
The admission of poor students sponsored by the Beca 18 social program into Lima universities is a recent phenomenon that requires studies on their adjustment and academic performance. This research targeted Beca 18 students at USIL and compared their responses to a questionnaire on perceptions of classroom climate with those from regular students. Both were participating in the course on math analysis offered to engineering students. In the general context of positive perceptions of classroom climate, Beca 18 students slightly differed from regular students, showing more positive perceptions of professor’s behavior in terms of creation of a working environment, class pace, interest in the student, and promotion of cooperation and group work. A greater difference was observed in regard of the avoidance of a climate of competition, which should be studied in greater depth. On the other hand, Beca 18 students complained more about the lack of solidarity, which can be explained by their adaptation to the more co lectivistic culture observed in Peruvian provinces.